2019
DOI: 10.1186/s12889-019-6985-9
|View full text |Cite
|
Sign up to set email alerts
|

Social support, mental health needs, and HIV risk behaviors: a gender-specific, correlation study

Abstract: Background The HIV/AIDS epidemic continues to threaten the health and wellbeing of millions in the United States and worldwide. Syndemic theory suggests that HIV/AIDS can cooccur with other afflictions. As close to 20% of US adults live with a mental health condition, it is critical to understand the correlation between HIV risk behaviors and mental health needs, as well as protective factors such as social support in intervening the association between mental distress and HIV risk behaviors. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 58 publications
4
32
0
Order By: Relevance
“…The implication of this is that an individual's support system which could be members of his/her family, close friend, colleague and so on does account for his or her self-esteem. Furthermore, Fang et al (2019), also revealed that social support was significant in their study on women's conceptions of coping with HIV scourge in daily life. One explanation for this could also be that seeking social support is one of the ways people cope with stressful situations, and this is evident in the number of women who seek social support interventions in most counseling organisations in the State.…”
Section: Discussionmentioning
confidence: 94%
“…The implication of this is that an individual's support system which could be members of his/her family, close friend, colleague and so on does account for his or her self-esteem. Furthermore, Fang et al (2019), also revealed that social support was significant in their study on women's conceptions of coping with HIV scourge in daily life. One explanation for this could also be that seeking social support is one of the ways people cope with stressful situations, and this is evident in the number of women who seek social support interventions in most counseling organisations in the State.…”
Section: Discussionmentioning
confidence: 94%
“…Social support networks comprise individuals who provide support resources such as financial, instrumental, emotional, and informational support when needed [17]. The findings of various studies have shown the protective effect and moderating role of social support in the face of adverse events and coping with stress [36]. Social support creates conditions that make one feel loved, cared for, and valued when needed [17].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, they are less likely than other people to be inflicted by physical, mental, and psychological disorders [38]. On the other hand, deprivation of emotional and social support can reduce one's ability to cope with stress and increases one's willingness to engage in risky behaviors such as substance abuse or a tendency to use more dangerous substances [36]. Alongside this, the results of some studies have indicated that some motivations for drug use in prison entail pain reduction, avoidance of problems, and feelings of belonging and acceptance in the social network of other drug addicts in the prison [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) is one of the most critical health concerns globally. [ 1 2 3 ] According to reliable estimates in 2014, the population of HIV/AIDS patients in Iran in common was 28,863 people. [ 4 5 ] Due to medical and health advances, many people with AIDS have entered old age.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it increases the risk of adverse events in their lives and chronic medical conditions. [ 2 10 ] People living with HIV are associated with many challenges such as social pressures, stigma and discrimination, depression, stress, loneliness, and early loss of the job, family, health, and physical appearance. [ 11 12 13 14 15 ] These people hide their illness because of the fear of social stigma and being rejected by family and society.…”
Section: Introductionmentioning
confidence: 99%